Tetraoksigenasi Santon dari Kulit Batang Garcinia nigrolineata Tetraoxygenated Xanthone from The Stem Bark of Garcinia nigrolineata - Muharni Muharni; Supriyatna Supriyatna; Husein Bahti; Dachrianus Dachrianus (Jurnal ILMU DASAR, 2009)
A tetraoxygenated xanthone, 1,7-dihidroxy-3-methoxy-4-(3methylbut-2-enyl),6’,6’ –dimethylpyrano (2’ , 3’ : 5, 6) xanthone had been isolated from the ethyl acetate extract of the stem bark of Garcinia nigrolineata Planch Ex T. Anders. The structure of these compounds were determined on the basis of spectroscopic NMR 1D and 2D.